Analisis Limbah Cair Domestik Kantin: Strategi Inovatif untuk Pengelolaan Lingkungan yang Berkelanjutan di Universitas Panca Bhakti - Rahsia, Shandra Andina; Anggraini, Ika Muthya; Marbun, Julianti (Universitas Tanjungpura, 2025)
The canteen at Universitas Panca Bhakti generates domestic wastewater from daily activities such as cooking, washing, and kitchen cleaning, which poses a potential threat to the environment. This study aims to identify the characteristics of the canteen's wastewater based on key pollutant parameters and to design a small-scale domestic wastewater treatment system in accordance with the quality standards set by the Ministry of Environment and Forestry Regulation No. 68 of 2016. The methodology includes wastewater sampling at three different operational times (morning, noon, and afternoon), followed by laboratory analysis of BODâ‚…, COD, TSS, oil and grease, pH, ammonia, and total coliform. The results show that all parameters exceeded the quality standard limits, with peak pollutant concentrations recorded at 3:00 PM